FUEL CONSUMPTION OF A TRACTOR ROTARY CUTTER IMPLEMENTED IN WEED MANAGEMENT IN ORCHARD OF BARBADOS-CHERRY (Malpighia Ermaginata) IN ORGANIC FARMING - Santos, L. F. A.; Batistas, C. D.; Vieira, A. D.; Fernandes, F. R. B.; Albiero, D. (Revista Brasileira de Engenharia de Biossistemas, 2017)
The culture of acerola has great importance for the country's fruit growing, mainly in the Northeast, where first the crop was established commercially in Brazil by the Rural University of Pernambuco in 1955. The control of weeds is of paramount importance for the good development of the cultures , In perennial crops this control is largely viable by the mechanical method, such as brushcutters, because the between planting lines have a necessary spacing for the tractor-implement set to perform such a process, this method shows the most viable, when compared to Manual and chemical control, since the machinery manages to treat a superior area of ​​the activity carried out manually by the man and from the environmental point of view, does not make use of dangerous substances to the environment as the herbicides used in the chemical treatment of weeds. The objective of this study was to evaluate the fuel consumption in a tractor-chopper assembly, with three types of brushcutter and four different combinations of gear and rotation, among the planting lines in a orchard of organic production of acerola in the municipality of Ubajara in the state of Ceará. The results showed that there was a significant difference in the consumptions of the treatments tested, which demonstrates the importance of this type of tests aiming at the economy in mechanized operations.